Can a training hub deliver undergraduate medical education with patient educators?. Issue 6 (2nd November 2022) - DaSilva, Debra; Roberts, Rachel; Jones, Melvyn; Yong, Joanna; Park, Sophie
ABSTRACT: Background: Medical schools may find it difficult to coordinate GP practices to support undergraduate medical education in primary care. In England, every Integrated Care System area now has a funded training hub to plan and upskill the primary care and community health workforce. We evaluated whether a training hub could help deliver undergraduate medical education, co-facilitated by patient educators. No published research has evaluated this model before. Methods: We used before and after surveys (617 students), interviews (28) and focus groups (20 people) with undergraduate medical students, patient educators and training hub and medical school team members. Findings: It was feasible for a training hub to develop and co-deliver a workshop with patient educators. 61% of Year 4 undergraduate students (first clinical year) took part, a high attendance rate during the COVID-19 pandemic. 80% of students said they learnt a lot about managing conditions in primary care and the community as a result. They particularly valued engaging with patient educators and seeing interprofessional working between GPs and pharmacists, which were cornerstones of the training hub approach. The hub was able to recruit and retain patient educators more effectively than the medical school alone. Patient educators said they felt valued and developed new skills. Conclusions: Working with training hubs may be part of the solution to issues medical schools face when organising undergraduate education about primary care. This small evaluation suggests that this model could be tested further.